2009
DOI: 10.1182/blood-2008-07-171066
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of collagen in factor XII–dependent thrombus formation

Abstract: In vivo mouse models have indicated that the intrinsic coagulation pathway, initiated by factor XII, contributes to thrombus formation in response to major vascular damage. Here, we show that fibrillar type I collagen provoked a dosedependent shortening of the clotting time of human plasma via activation of factor XII. This activation was mediated by factor XII binding to collagen. Factor XII activation also contributed to the stimulating effect of collagen on thrombin generation in plasma, and increased the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
174
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 47 publications
(59 reference statements)
4
174
0
Order By: Relevance
“…Mangin et al (40) reported that thrombin was able to compensate for the effect of GPVI/FcR␥ deficiency in mouse platelets in in vivo models of thrombosis. The mechanism we describe, selective enhancement of the adhesive activity of the ␣ 2 ␤ 1 integrin via PAR4 activation, is the likely explanation for the observations of van der Meijden et al (39) and Mangin et al (40).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Mangin et al (40) reported that thrombin was able to compensate for the effect of GPVI/FcR␥ deficiency in mouse platelets in in vivo models of thrombosis. The mechanism we describe, selective enhancement of the adhesive activity of the ␣ 2 ␤ 1 integrin via PAR4 activation, is the likely explanation for the observations of van der Meijden et al (39) and Mangin et al (40).…”
Section: Discussionmentioning
confidence: 51%
“…This mechanism is further supported by the recent findings regarding the role of thrombin in platelet adhesion to collagen under conditions of flow. Van der Meijden et al (39) described separate but complimentary roles of thrombin produced subsequent to the contact activation of factor XII by collagen, and GPVI/FcR␥ signaling on human platelet adhesion to collagen. Furthermore, inhibition of thrombin resulted in diminished platelet adhesion to collagen.…”
Section: Discussionmentioning
confidence: 99%
“…15,38 In order to investigate the role of FVIII in this process, we used citrate-anticoagulated blood from F8 -/-or F8 +/+ mice and made this flow during recalcification over collagen at an intermediate wall-shear rate (1000 s -1 ). The blood samples were supplemented with a surplus of 10 pM tissue factor to stimulate the extrinsic pathway.…”
Section: Key Roles Of Murine Factors VIII and Ix In The Formation Of mentioning
confidence: 99%
“…37 Samples of citrate-anticoagulated blood (400-1500 μL) were made to flow at defined wall-shear rate, as described for murine 38 …”
Section: Whole Blood Flow Chamber Experimentsmentioning
confidence: 99%
“…Three interesting possibilities have been discussed but not fully validated. Fibrillar collagen is thought to activate FXII in addition to activating platelets (15), neutrophil extracellular traps (NETs) are negatively charged and could thereby trigger FXII activation (16) and activated platelets may induce coagulation through FXII by the release of polyphosphates. However the platelet-induced activation has been debated, it was originally postulated by Müller et al (17) and has thereafter been contradicted by our research group, Faxälv et al (18).…”
Section: The Secondary Haemostasismentioning
confidence: 99%